Functional Characterization of Lysophosphatidylcholine: Acyl-CoA Acyltransferase Genes From Sunflower (Helianthus annuus L.) - Mapelli-Brahm, Ana; Sánchez, Rosario; Pan, Xue; Moreno-Pérez, Antonio J.; Garcés, Rafael; Martínez-Force, Enrique; Weselake, Randall J.; Salas, Joaquín J.; Venegas-Calerón, Mónica (Frontiers in Plant Science, 2020)
Lysophosphatidylcholine acyltransferase (LPCAT, EC 2.3.1.23) is an evolutionarily conserved key enzyme in the Lands cycle that catalyses acylation of lysophosphatidylcholine (LPC) to produce phosphatidylcholine (PC), the main phospholipid in cellular membranes. In this study, three LPCAT genes from sunflower were identified and the corresponding proteins characterized. These HaLPCAT genes encoded functionally active enzymes that were able to complement a deficient yeast mutant. Moreover, enzymatic assays were carried out using microsomal preparations of the yeast cells. When acyl specificities were measured in the forward reaction, these enzymes exhibited a substrate preference for unsaturated acyl-CoAs, especially for linolenoyl-CoA, while in the reverse reaction linoleoyl or linolenoyl acyl groups were transferred from PC to acyl-CoA to a similar extent. Expression levels of LPCAT genes were studied revealing distinct tissue-specific expression patterns. In summary, this study suggests that the combined forward and reverse reactions catalysed by sunflower LPCATs facilitate acyl-exchange between the sn-2 position of PC and the acyl-CoA pool. Sunflower LPCATs displayed different characteristics, which could point to different functionalities, favouring the enrichment of seed triacylglycerols with polyunsaturated fatty acid.